Optical and near-infrared photometric monitoring of the transient X-ray binary A0538-66 with REM - Ducci, L.; Covino, S.; Doroshenko, V.; Mereghetti, S.; Santangelo, A.; Sasaki, Manami (Astronomy & Astrophysics, 2016)
The transient Be/X-ray binary A0538-66 shows peculiar X-ray and optical variability. Despite numerous studies, the intrinsic properties underlying its anomalous behaviour remain poorly understood. Since September 2014 we have conducted the first quasi-simultaneous, optical and near-infrared photometric monitoring of A0538-66 in seven filters with the Rapid Eye Mount ( REM) telescope to understand the properties of this binary system. We found that the REM light curves show fast flares lasting one or two days that repeat almost regularly every similar to 16.6 d, which is the orbital period of the neutron star. If the optical flares are powered by X-ray outbursts through photon reprocessing, the REM light curves indicate that A0538-66 is still active in X-rays; bright X-ray flares (L-x greater than or similar to 10(37) erg s(-1)) could be observable during the periastron passages. The REM light curves show a long-term variability that is especially pronounced in the g-band and decreases with increasing wavelength until it no longer appears in the near-infrared light curves. In addition, A0538- 66 is fainter with respect to previous optical observations, and this is likely because of the higher absorption of the stellar radiation of a denser circumstellar disc. On the basis of the current models, we interpret these observational results with a circumstellar disc around the Be star observed nearly edge-on during a partial depletion phase. The REM light curves also show short-term variability on timescales of similar to 1 day, which is possibly indicative of perturbations in the density distribution of the circumstellar disc caused by the tidal interaction with the neutron star.
Keywords: accretion; accretion disks; X-rays: binaries; (stars:) pulsars: individual: A0538-66